2015
DOI: 10.1088/0953-2048/28/6/065007
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and field-dependent characterization of a conductor on round core cable

Abstract: The Conductor on Round Core (CORC) cable is one of the major high temperature superconductor cable concepts combining scalability, flexibility, mechanical strength, ease of fabrication and high current density; making it a possible candidate as conductor for large, high field magnets. To simulate the boundary conditions of such magnets as well as the temperature dependence of Conductor on Round Core cables a 1.16 m long sample consisting of 15, 4 mm wide SuperPower RE BCO tapes was characterized using the "FBI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…To get better understanding of the magnetization and thermal stability, a three-dimensional time dependent thermalelectric network model of coated conductor cable structures is developed. The model is capable of simulating Roebel, CoRC [14] and Stacked (twisted) type of cables.…”
Section: Introductionmentioning
confidence: 99%
“…To get better understanding of the magnetization and thermal stability, a three-dimensional time dependent thermalelectric network model of coated conductor cable structures is developed. The model is capable of simulating Roebel, CoRC [14] and Stacked (twisted) type of cables.…”
Section: Introductionmentioning
confidence: 99%
“…REBCO (RE-Ba 2 -Cu 3 -O x , RE: rare Earth) coated conductor has been regarded as one of the most viable high-temperature superconductor (HTS) options for next-generation high field magnets, mainly owing to its large in-field current carrying capacity and mechanical robustness. Commercial REBCO tapes show a 95% critical current (I c ) retention strain of 0.5% or higher, which corresponds to a tensile stress of 550-850MPa depending on the tape's architecture [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the critical current drops significantly at the strain of 0.6%. The effect of axial strain on the critical current in a high-temperature superconductor for electric power application was studied in [ 30 ]. It was presented that the strain 0.33% significantly limits the critical current.…”
Section: Design Of the Busbar Compensation Loopmentioning
confidence: 99%